Assessing Flipped Versus Traditional Classrooms: Is Flipping Really Better? - Poniatowski, Kelly (Journalism & Mass Communication Educator, 2019)
Using a quasi-experiment, this research looks at grades and student satisfaction over the course of six semesters in a college-level writing class. Three of the classes were taught traditionally, and the other three classes utilized the flipped classroom concept. All classes were taught by the same instructor. Using independent samples t tests, results indicate that students received higher grades and had more satisfaction in the traditional classroom.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMDc3Njk1ODE5ODM1MDM3